2020
DOI: 10.1209/0295-5075/130/50003
|View full text |Cite
|
Sign up to set email alerts
|

Non-locality and time-dependent boundary conditions: A Klein-Gordon perspective

Abstract: The dynamics of a particle in an expanding cavity is investigated in the Klein-Gordon framework in a regime in which the single-particle picture remains valid. The cavity expansion represents a time-dependent boundary condition for the relativistic wave function. We show that this expansion induces a non-local effect on the current density throughout the cavity. Our results indicate that a relativistic treatment still contains apparently spurious effects traditionally associated with the unbounded velocities i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The disappearance of Klein tunneling in the infinite well limit should also be of interest to recent works that have studied the Klein-Gordon equation in a box with moving walls [14][15][16] (the special boundary conditions chosen in these works were indeed not justified).…”
Section: Discussionmentioning
confidence: 99%
“…The disappearance of Klein tunneling in the infinite well limit should also be of interest to recent works that have studied the Klein-Gordon equation in a box with moving walls [14][15][16] (the special boundary conditions chosen in these works were indeed not justified).…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, spin-zero particles are described in relativistic quantum theory by the Klein-Gordon equation (KGE) (see the textbooks 8,12 and Refs. 13,14 for very recent work). Constructing a broad wave packet from the scattering solution of the Klein-Gordon equation (KGE), and choosing the mean energy to be a half of the barrier's height, E = V /2 , we find the particle not only transmitted without reflection, but also advanced relative to free propagation by twice the barrier's width d (see Fig.…”
Section: Klein Paradox For Bosons Wave Packets and Negative Tunnellimentioning
confidence: 99%
“…Similarly, it can be shown that the last WP moving to the left emerged at x = 0 at about the same time the incident WP arrived there. Now we can reconstruct the scenario described by the divergent MRE (13). Initially, there is not only a WP approaching the barrier from the left, but also another wave packet, already trapped in the barrier region.…”
Section: Unbound Solutions Of the Schrödinger Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reason for choosing this system is that analytic solutions of the time-dependent Schrödinger equation are known [8]. The second, less mundane, reason is that such systems, and in particular their simplest variant (a box with a linearly moving wall), have long been suspected of manifesting some form of nonlocality [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%